Parental and physician's point-of-view towards antibiotic prescriptions and discharge conversations in the pediatric emergency department - Daphne Peeters; Lars M. A. van Scheppingen; Gertjan J. A. Driessen; Lilly M. Verhagen (BMC, 2022)
Abstract Background Within Europe, the Netherlands has one of the lowest antibiotic consumption rates. We aimed to gain insight into attitudes of Dutch physicians and parents towards information provided during discharge conversations in the emergency department (ED) and towards antibiotic use in children, in order to obtain information on the assumptions and beliefs that underlie a practice of low prescription rates. Methods Discharge conversations of 70 children presenting with an infectious disease at the ED were observed. After 7-10 days, 55 parents were called for a semi-structured interview. In addition, 29 pediatricians and pediatric residents completed a questionnaire on their prescription behaviour. Results Concerns about (recognizing) the severity of their child's infection was parents' main motivation to seek help. Both pediatricians and parents reported a general reluctance towards antibiotic use. While pediatricians took appropriateness based on indication and the risk of antimicrobial resistance development into account when considering antibiotic treatment, a thorough medical assessment was deemed more important for Dutch parents than any type of therapeutic treatment, including antibiotics. The topic most often discussed during the discharge conversations was safety netting instructions (in 86%), which were discussed more often during discharge conversations with parents of children that did not receive antibiotic treatment (91% versus 69%). Conclusion Dutch pediatricians and parents are both reluctant to use antibiotics for uncomplicated infections in children, but for different reasons. The emphasis of discharge conversations was on safety netting instructions, which seems to be an alternative for (early) antibiotic use in our setting and may guide overuse prevention strategies in settings where antibiotic overuse is more common.